A severe neurodegenerative disease with Lewy bodies and a mutation in the glucocerebrosidase gene - Sipilä Jussi OT; Kytövuori Laura; Rauramaa Tuomas; Rauhamaa Hugo; Kaasinen Valtteri; Majamaa Kari (NATURE PORTFOLIO, 2025)
Several heterozygous variants of the glucocerebrosidase gene (GBA1) have been reported to increase the risk of Parkinson's disease (PD) and dementia with Lewy bodies (DLB). GBA1-associated PD has been reported to be more severe than idiopathic PD, and more deleterious variants are associated with more severe clinical phenotypes. We report a family with a heterozygous p.Pro454Leu variant in GBA1. The variant was associated with a severe and rapidly progressive neurodegenerative disease with Lewy bodies that were clinically and pathologically diverse. Pathogenicity prediction algorithms and evolutionary analyses suggested that p.Pro454Leu is deleterious.